Warfarin treatment and migraine. Issue 819 (January 1994) - Suresh, C. G.; Neal, D.; Coupe, M. O.
Abstract : A patient suffering from migraine, whose symptoms were abolished by warfarin therapy, is reported. Warfarin was prescribed for deep vein thrombosis and the frequency of the patient's headache improved remarkably during the anticoagulant therapy. Because of the unusual nature of the response to anticoagulant therapy, warfarin was reintroduced on a double blind (versus placebo) basis and once again abolished the headaches.